A Comparative Study of the Effectiveness of Using Traditional and Digital Learning Media - Wardi; Setiyono, Nabella Angellita (Yayasan Meira Visi Persada, 2025)
This research discusses the comparison of the effectiveness of using traditional and digital learning media. The main purpose of this research is to provide an overview of the comparison of the effectiveness of the use of traditional and digital learning media. The research method used is a literature study. The research was conducted by reading journals, books, or other sources related to the use of traditional and digital learning media. The references used include six scientific articles published in the range of 2023 to 2024. This literature study was conducted to understand more deeply the effectiveness of using traditional and digital-based learning media. The results of the study can provide insights into the development of learning strategies that are more effective and adaptive to technological developments.